2019
DOI: 10.4236/ojce.2019.94019
|View full text |Cite
|
Sign up to set email alerts
|

Patron Survey of Acceptable Wait Times at Transit Bus Stops in the District of Columbia

Abstract: The wait time of bus patrons at bus stops is one of several measures for assessing reliability of transit services, especially in urban areas. The uncertainty associated with waiting affects bus patrons' perception of quality of the service provided. Studies in this subject area have therefore been of interest to transit service agencies and officials. This paper presents the findings of a study conducted to determine patrons' maximum acceptable wait times (beyond the scheduled arrival time) at bus stops in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Whether a transit priority request was rejected is meaningless to a customer; what matters is whether the travel time was reduced and/or less variable. Agencies such as Washington Metropolitan Area Transit Authority and Metropolitan Transportation Authority have also applied high-frequency AVL technology to measure travel time and control delay reduction based on the bus location and speed ( 18 ). The MBTA AVL data updates every 6 s and does not include detailed bus information (i.e., door state).…”
Section: Resultsmentioning
confidence: 99%
“…Whether a transit priority request was rejected is meaningless to a customer; what matters is whether the travel time was reduced and/or less variable. Agencies such as Washington Metropolitan Area Transit Authority and Metropolitan Transportation Authority have also applied high-frequency AVL technology to measure travel time and control delay reduction based on the bus location and speed ( 18 ). The MBTA AVL data updates every 6 s and does not include detailed bus information (i.e., door state).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the percentage of passengers who tend to pay more or wait. According to Arhin et al (2019), the maximum acceptable waiting time at peak hours was found 20 minutes. Herein, at peak hours, 46.67% of the mini-buses had unacceptable waiting times and about 53.33% had acceptable waiting times.…”
Section: Waiting Time Measurementioning
confidence: 99%
“…Unpredictable traffic conditions can cause a delay in service frequency and consequently increase travel time to arrive at a selected destination. Arhin et al (2019) developed a regression model for determining the maximum acceptable waiting time depending on average headway, temperature, bus arrival time and presence of shelter. They found that the maximum acceptable waiting time of bus patrons at bus stops was 20 minutes and about 33% of the studied sample said that the most appropriate waiting time for the passengers was around 5 minutes beyond the scheduled arrival time of buses.…”
Section: Introductionmentioning
confidence: 99%